Supplementation of fish meal and exogenous administration of COX-2 inhibitor on conception rate in repeat breeding Jersey crossbred cows - T. Sarath; N. Arunmozhi; Cecilia Joseph; S. Rangasamy; R. Suresh Kumar; C. Pugazharasi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted on repeat breeding cows at Large Animal Gynaecology Ward, Department of Clinics, Madras Veterinary College, Chennai and some private cattle farms in and around Koduvalli region, Tiruvallur district, Tamil Nadu. In experiment I, Jersey crossbred cows (n=31) synchronized by PGF2a and inseminated on exhibited estrum. The cows were randomly divided into five groups viz. Group I (control, n=6), group II (n=7,100mg), group III (n=6, 150mg), group IV (n=6, 200mg) and group V (n=6, 250mg) and supplemented with fish meal on day 13, 14 and 15 of post insemination in addition to their routine feed. Pregnancy diagnosis was carried out by rectal palpation on day 60 of post insemination. In experiment II, twelve repeat breeding Jersey crossbred cows were selected and synchronized using PGF2a followed by timed insemination. On day 10 of post estrus, rectal examination was performed to identify the corpus luteum and randomly divided into two group viz. Group I and Group II (control). Group I cows were injected with Meloxicam @ 0.5 mg/ kg body weight through intramuscularly on day 13 to 15 post-insemination. The conception rate in experiment I as in Group I, group II, group III, group IV and group V are 16.67%, 71.43%, 66.67%, 66.67% and 50.0%, respectively. The conception rate in meloxicam treated animal was 66.7% and in control animal was 33.3%. The fish meal treatment and Cox-2 inhibitor in repeat breeding crossbred cows had improved the conception rate. Further, the supplementation of 100mg offish meal in repeat breeding cows has shown higher conception rate as compared to other groups in experiment II. Hence, it may be used in field condition for enhancement of conception rate, however, further studies in larger population is warranted.